2012
DOI: 10.4236/as.2012.35090
|View full text |Cite
|
Sign up to set email alerts
|

Baru almonds from different regions of the Brazilian Savanna: Implications on physical and nutritional characteristics

Abstract: While some reports show that physical characteristics of the baru fruits (<i>Dipteryx alata</i> Vog.) differ within and among the Brazilian Savanna regions, a study shows that there are differences in the nutritional composition of baru almonds from different trees from the same Savanna area. It is unknown, however, whether the Savanna’s region influences the nutritional quality of this native almond. Thus, we evaluated the influence of East, Southeast and West regions of the Brazilian Savanna on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…The NPR values of the test rations found were also significantly lower than that of the control group (casein) but similar to that reported for the proteins of baru almond (2.76) (Czedera et al, 2012).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The NPR values of the test rations found were also significantly lower than that of the control group (casein) but similar to that reported for the proteins of baru almond (2.76) (Czedera et al, 2012).…”
Section: Resultssupporting
confidence: 87%
“…The content of all essential amino acids was higher than those recommended by FAO/WHO. Sulphurated Amino Acids (SAA) are limiting factors in many food plants such as soy (Friedman & Brandon, 2001), beans, other vegetables (Sgarbieri, 1987), and nuts (Fernandes et al, 2010;Czedera et al, 2012). The level of sulphurated amino acids (methionine + cysteine) of the raw bacuri almond protein was 33.9 %; this value is higher than that established by the FAO/WHO and those found for beans (19.95 %), wheat (18.12 %), corn (22.21 %), soy (18.65 %), and it was close to that found for beef (35.59 %) (Pires et al, 2006).…”
Section: Biological Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The improved protein quality of autoclaved BAF, estimated by NPR and PDCAAS, is a result of the protein digestibility improved by the heating process (autoclaving), which induces the inactivation of antinutrients and the desnaturation of proteins (Muzquiz et al, 2012). Czeder et al (2012) investigated the protein quality of roasted baru almonds from the southeast area of Goiás State by NPR, and the authors found a value of 2.76, which is comparable to that of autoclaved BAF (Table 6). PDCAAS value of autoclaved BAF (81%) was higher than those found in the literature for whole baru almond, from 65% to 73% .…”
Section: Discussionmentioning
confidence: 92%
“…The lack of sample stratification is an important limitation in food research, mainly for native fruits, since studies on the biodiversity of the Brazilian Savanna have shown that there is a great variability of physical (Moura et al, 2013;Vera et al, 2005) and chemical (Czeder et al, 2012) properties of the native fruits from different area of the biome. Therefore, this study tested the hypothesis that there are differences in colour, chemical properties and antioxidant activity of pequi fruits from different regions of the Brazilian Savanna, and that these properties are interrelated.…”
Section: Introductionmentioning
confidence: 99%